PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENERAPAN AKUNTANSI AKRUAL DENGAN PERANGKAT PENDUKUNG SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PEMERINTAH KOTA YOGYAKARTA) - Dwi Sudaryati; Sucahyo Heriningsih (Optimum: Jurnal Ekonomi dan Pembangunan, 2014)
This study aims to empirically examine the effect of human resource competencies to the successful implementation of accrual accounting (PP 71 of 2010) with the support device as a moderating variable in the Local Government of Yogyakarta city. The population in this study was a head on education and KDP staff sectors in the local government area of the city of Yogyakarta is involved in the process of preparation of the financial statements. Sampling technique using simple random sampling and testing hypotheses using multiple regression analysis (multiple regression). The results of this study prove that the human resource competencies significantly influence the successful implementation of Accrual Accounting (PP 71 of 2010). However, the competence of human resources associated with the device does not support a significant effect on the successful implementation of Accrual Accounting (PP 71 of 2010). The result is expected, can assist policy makers in understanding the factors that support the successful implementation of accrual accounting rate (PP 71 In 2010, the Government Accounting Standards berbasis full acrual).